Risk assessment after a severe hospital-acquired infection associated with carbapenemase-producing Pseudomonas aeruginosa - Hopman, J; Meijer, C; Kenters, N; Coolen, JPM; Ghamati, MR; Mehtar, S; van Crevel, R; Morshuis, WJ; Verhagen, AFTM; van den Heuvel, MM; Voss, A; Wertheim, HFL (American Medical Association, 2019)
Importance Resistance of gram-negative bacilli to carbapenems is rapidly emerging worldwide. In 2016, the World Health Organization defined the hospital-built environment as a core component of infection prevention and control programs. The hospital-built environment has recently been reported as a source for outbreaks and sporadic transmission events of carbapenemase-producing gram-negative bacilli from the environment to patients. Objective To assess risk after the identification of an unexpected, severe, and lethal hospital-acquired infection caused by carbapenemase-producing Pseudomonas aeruginosa in a carbapenemase-low endemic setting. Design, Settings, and Participants A case series study in which a risk assessment was performed on all 11 patients admitted to the combined cardiothoracic surgery and pulmonary diseases ward and the hospital-built environment in the Radboud University Medical Center, the Netherlands, in February 2018. Exposures Water and aerosols containing carbapenemase-producing (Verona integron-mediated metallo-β-lactamase [VIM]) P aeruginosa. Main Outcomes and Measures Colonization and/or infection of patients and/or contamination of the environment after the detection of 1 patient infected with carbapenemase-producing (VIM) P aeruginosa. Results A total of 5 men (age range, 60-84 years) and 6 women (age range, 55-74 years) were admitted to the combined cardiothoracic surgery and pulmonary diseases ward. The risk assessment was performed after carbapenemase-producing (VIM) P aeruginosa was unexpectedly detected in a man in his early 60s, who had undergone a left-sided pneumonectomy and adjuvant radiotherapy. No additional cases (colonization or infection) of carbapenemase-producing (VIM) P aeruginosa were detected. Plausible transmission of carbapenemase-producing P aeruginosa from the hospital environment to the patient via the air was confirmed by whole-genome sequencing, which proved the relation of Pseudomonas strains from the patient, the shower drains in 8 patient rooms, 1 sink, and an air sample. Conclusions and Relevance This study suggests that rethinking the hospital-built environment, including shower drains and the sewage system, will be crucial for the prevention of severe and potential lethal hospital-acquired infections.